Diseño de una planta móvil de potabilización de agua - Espinoza C., A. (2011)
The present paper show the design of mobile plant water purification for use in emergency or disaster situations where the main requirement that evidence is the lack of potable water, provides the advantage of being put into operation in a few hours, easy to use , not requires power because it has a generator and when it is appropriate within a 20 foot container can be easily moved from one place to another. To determinate the stages of purification, such as the Bulu-Bulu, Jujan and Chimbo was determinate based on consumption per capita given by PAHO to emergency situations and thus has the capacity to supply 300 families with a flow of With the use of this plant was achieved savings of 97% compared to water by bottles